(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
Chronic pain is a complex phenomenon that involves multiple biological, neurochemical, emotional, psychosocial and sociocultural elements. This pathology causes social, family and professional losses in the life of those who suffer it. The present study aimed to highlight the importance of intervention strategies used by Acceptance and Commitment Therapy (ACT) in order to develop the therapeutic process, using a chronic pain case study. Therefore, a historical overview about this disease evolution in our civilization was conducted and chronic pain was conceptualized, classified and explained according to the Clinical Behavior Analysis perspective. Forty-three psychotherapy sessions were carried out in a period of 1 year and 10 months. The molecular and molar functional analysis, the understanding of historical and actual contingencies, provided access to the establishing and maintaining conditions of the patient´s behavioral patterns which enable the permanence of the chronic pain. Based on this, therapeutic interventions used by ACT were of fundamental importance to the patient quality of life improvement: they promoted emotional tolerance and acceptance in relation to the physical and emotional states experienced by the patient as well as enabled relevant behavioral changes